1998
DOI: 10.1046/j.1365-2265.1998.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary adrenal insufficiency associated with autoimmune disorders: a report of twenty‐five cases

Abstract: The co-existence of autoimmune disorders with secondary adrenal insufficiency suggests an autoimmune aetiology for the ACTH deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
(22 reference statements)
1
15
0
2
Order By: Relevance
“…This observation is consistent with a recent Japanese review of the literature, which reported that 24% of cases of isolated ACTH deficiency were associated with hypothyroidism, most commonly Hashimoto's thyroiditis (6). Similarly, thyroid autoimmunity, with or without subclinical or overt hypothyroidism, was found in , 25% of Polish patients with secondary adrenal insufficiency of uncertain aetiology (2). As cortisol is a physiological regulator of thyrotrophin secretion (1), resolution of biochemical hypothyroidism following adequate glucocorticoid therapy has been reported (32 -34) and thyroid function should therefore be reassessed after adequate glucocorticoid replacement.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This observation is consistent with a recent Japanese review of the literature, which reported that 24% of cases of isolated ACTH deficiency were associated with hypothyroidism, most commonly Hashimoto's thyroiditis (6). Similarly, thyroid autoimmunity, with or without subclinical or overt hypothyroidism, was found in , 25% of Polish patients with secondary adrenal insufficiency of uncertain aetiology (2). As cortisol is a physiological regulator of thyrotrophin secretion (1), resolution of biochemical hypothyroidism following adequate glucocorticoid therapy has been reported (32 -34) and thyroid function should therefore be reassessed after adequate glucocorticoid replacement.…”
Section: Discussionsupporting
confidence: 79%
“…It is most commonly observed during or after chronic administration of exogenous glucocorticoids and in patients with hypothalamic-pituitary tumours, often in association with other pituitary hormone deficits (1). Presenting symptoms are variable and non-specific and include fatigue, reduced strength, myalgia, arthralgia, weight loss, anorexia, postural dizziness and neuroglycopaenia (1,2). The diagnosis is suspected by finding a low morning cortisol in the absence of adrenocorticotropic hormone (ACTH) elevation and is confirmed by the demonstration of suboptimal cortisol levels following dynamic testing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Most cases are secondary to autoimmune process such lymphocytic hypophysitis. [3,4] It may also occur after traumatic head injury [5] and pituitary irradiation. [6] Genetic cases are encountered in neonatal and childhood isolated ACTH deficiency.…”
Section: Introductionmentioning
confidence: 99%